Rapidly sequence-controlled electrosynthesis of organometallic polymers - Zhang, Jian; Wang, Jinxin; Wei, Chang; Wang, Yanfang; Xie, Guanyu; Li, Yongfang; Li, Mao (Nature communications, 2020)
Single rich-stimuli-responsive organometallic polymers are considered to be the candidate for ultrahigh information storage and anti-counterfeiting security. However, their controllable synthesis has been an unsolved challenge. Here, we report the rapidly sequence-controlled electrosynthesis of organometallic polymers with exquisite insertion of multiple and distinct monomers. Electrosynthesis relies on the use of oxidative and reductive C–C couplings with the respective reaction time of 1 min. Single-monomer-precision propagation does not need protecting and deprotecting steps used in solid-phase synthesis, while enabling the uniform synthesis and sequence-defined possibilities monitored by both UV–vis spectra and cyclic voltammetry. Highly efficient electrosynthesis possessing potentially automated production can incorporate an amount of available metal and ligand species into a single organometallic polymer with complex architectures and functional versatility, which is proposed to have ultrahigh information storage and anti-counterfeiting security with low-cost coding and decoding processes at the single organometallic polymer level. The controllable synthesis of organometallic polymers that can be used in ultrahigh information storage and anti-counterfeiting security has been an unsolved challenge. Here, the authors show sequence-controlled electrosynthesis of organometallic polymers with exquisite insertion of multiple and distinct monomers.